Influência do tratamento com abatacept no reparo de úlceras traumáticas em mucosa jugal de ratos - Mesquita, Karine Cestaro (2018)
Abatacept is known for the regulation of T cell activation and modulation of inflammatory cytokines, and due to this to mechanisms it may interferes on wound healing. The aim of this study was to evaluate the ulcer’s healing process on buccal mucosa of males Wistar rats administered with Abatacept subcutaneously. The rats were randomized between a control group, injected with saline subcutaneously, and other three study groups, administered with Abatacept subcutaneously in the doses of 3.2 (ABA 3.2), 8 (ABA 8) and 20 mg/kg/week (ABA 20). The administration of saline and Abatacept was performed 14 days before oral ulcer induction and continued until euthanasia, performed on days 1, 3, 7, 14 and 21 after the ulcer induction. Oral ulcers of 8 mm diameter and 2 mm deep were induced on the left buccal mucosa. Ulcer diameter, body mass variation, Picrosirius red, immunohistochemistry for iNOS, interleukin (IL) 1 beta, IL 6, IL 10, CD8 and CD30, vascular permeability and blood count were recorded. Histological slides were performed for histopathological (scores) and histomorphometric analysis, such as: polymorphonuclear, mononuclear, angiogenesis and fibroplasia. ANOVA-1-way and -2-way/Bonferroni and Kruskal-Wallis/Dunn were used in the statistical analysis (GraphPad Prism 5.0®, p<0.05). Abatacept administration decreased ulcer diameter (p<0.001), polymorphonuclear (p<0.001) and mononuclear count (p=0.027), CD8+/CD30+ relation (p<0.001) and vascular permeability (p<0.001). However, the collagenesis (p<0.001) and IL-10 expression levels (p=0.016) increased on days 3 and 7. In the ABA 20 group, the over Abatacept doses were related to late wound healing (p<0.001), reduced angiogenesis (p=0.017) and extended period of high levels of iNOS (p=0.026), IL 1 beta (p=0.007) and IL 6 (p<0.001). This study demonstrated that Abatacept accelerates ulcer healing on the buccal mucosa of male Wistar rats due to the reduced migration of inflammatory cells, meanwhile, higher doses were associated with delayed repair and extended expression of proinflammatory cytokines.